Pengaruh Metode Pembelajaran Problem Based Learning Terhadap Peningkatan Keterampilan Literasi pada Mata Pelajaran Akidah Akhlak Kelas XI MAS TPI - Julaiha Panjaitan (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Madrasah Aliyah Swasta Taman Pendidikan Islam Medan shows that learning Akidah Akhlak in class XI is still textual and has not encouraged active student participation. Teachers use more thematic books as the main source of learning without linking them to contextual phenomena that are close to students' lives. As a result, students have difficulty understanding the material, such as the topic of funeral prayers. This can be seen from the students' daily test scores which only reach an average of 45, far below the Minimum Completion Criteria set by the school, which is 75. The research method is quantitative, this method can be interpreted as a research method based on the philosophy of positivism, used to research certain populations or samples, sampling techniques are generally carried out randomly. The conclusion of this study shows the average posttest score of students who are given learning using the problem based learning method (experimental class). This shows that there is a difference between student learning outcomes in the subject of Akidah Akhlak in the experimental class when compared to the learning outcomes of Islamic Religious Education in the control class. Thus, the use of problem based learning methods in learning akidah akhlak is more effective than learning using conventional approaches in an effort to improve the learning outcomes of class XI students at Taman Pendidikan Islam Private Islamic Senior High School. So it can be concluded that there is an Influence of the Use of Problem Based Learning Methods on Improving Literacy Skills in the Subject of Akidah Akhlak in the Experimental Class with the Control Class at Taman Pendidikan Islam Private Islamic Senior High School.